Pendampingan Pengembangan Keterampilan Membaca,Menulis, dan Menghafal di Madrasah Diniyah Al-Hidayah dukuh Krajan sukorejo - Rayi Ambarwati; Rinesti Witasari (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to improve the literacy and language proficiency of students in reading, writing, and memorizing. Building a strong foundation in understanding and mastering religious science and general knowledge. The high interest in learning Madin Hidayah students makes there almost no obstacles in it. The method in this study uses a qualitative method with data collection techniques, namely observation and interviews. The result of this research is that the support and involvement of parents and the community will strengthen the enthusiasm of the students. Students who received assistance will show significant improvement in reading, writing, and memorization skills compared to students who do not receive assistance